Pengembangan Bahan Ajar Pementasan Drama berbantuan QR Code pada Siswa Kelas XI di MA Al-Muhajirin Tugumulyo - Suci Triara Rahayu; Dewi, Rusmana; Inda Puspita Sari (LP3MKIL, 2022)
ABSTRACT This development thesis aims to describe the lesson material for the QR Code-assisted drama staging module. The research method used is Development Research (DR) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation. The module teaching materials are implemented in class XI Religion students at MA Al-Muhajirin Tugumulyo. The research instrument used is interviews while the data analysis is seen from the aspects of the validity test and the aspect of practicality testing. The results of the study prove that the teaching materials for the drama performance module assisted by QR Code are valid and practical with the assessment of material experts conducted by Mrs. Dr. Satinem, M.Pd. The average V results 0.78, the assessment of the design expert validator conducted by Dr. Dodik Mulyono, M.Pd. by the average V result of 0.70, and the validator conducted by the linguist, namely Mr. Agung Nugroho, M. Pd. the average is 0.75 and the percentage of practicality in the small group test is 78% and the percentage in the large group test is 76,6%.Overall this research is that this teaching material module can be used.